2019
DOI: 10.18488/journal.62.2019.66.316.334
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Behavioural Intention to Adopt Mobile Banking in Rural Sub-Saharan Africa Using an Extension of Technology Acceptance Model: Lessons from Zimbabwe

Abstract: The zeitgeist of mobile banking epoch in Sub-Saharan Africa has marked a fundamental transition from the use of physical currency, debit/credit cards and cheques towards a mobile banking e-commerce. In these countries mobile banking provides consumers with added-on advantages such as user-friendliness, cost effective, fast transaction speeds and increased customer satisfaction. Despite the popularity of mobile banking, consumers in most rural areas have largely remained excluded from such beneficial financial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
1
5
0
1
Order By: Relevance
“…Convenience may appear as an essential enabler in developed regions. However, for citizens in developing regions, it is mostly appreciated for its ability to reduce travel time and brokerage costs (Muzurura & Chigora, 2019). This study shared the same sentiment; convenience was found to be one of the enablers that motivate elderly consumers to adopt and use mobile banking.…”
Section: Enablers For Mobile Banking Adoptionsupporting
confidence: 58%
“…Convenience may appear as an essential enabler in developed regions. However, for citizens in developing regions, it is mostly appreciated for its ability to reduce travel time and brokerage costs (Muzurura & Chigora, 2019). This study shared the same sentiment; convenience was found to be one of the enablers that motivate elderly consumers to adopt and use mobile banking.…”
Section: Enablers For Mobile Banking Adoptionsupporting
confidence: 58%
“…This innovation is able to present a standardization of banking products and services in the form of innovation in the financial sector, known as mobile banking or M-banking (Mohammadi, 2015). Mobile banking is an innovative method of accessing banking services and products such as checking balances, bill payments, money transfers, account management, and other financial transaction activities through mobile phones anytime and anywhere (Muzurura & Chigora, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In our model, we assume that utility differences among different rural students determine the probability of selecting an adopting decision amongst a series of discrete choices. The basic conceptual framework of the multinomial logistic model was generalized from binary logistic regression done (Muzurura & Chigora, 2019). Following also a methodology that was popularized by Muzurura (2019) we selected the "NAMLS" decision as the baseline category against which an individual's decision to adopt MLSs was compared.…”
Section: Mathematical Model Frameworkmentioning
confidence: 99%
“…A number of studies that focus on developing countries suggest that mobile based learning systems are effective educational tools that can be used to improve learning effectiveness and efficiency for disadvantaged rural students and those students with specific learning difficulties or disabilities (Muzurura & Chigora, 2019). More than half of the rural student population in developing countries does not have adequate educational resources and also face barriers related to finance.…”
mentioning
confidence: 99%